2013
DOI: 10.1016/j.ajhg.2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in LRPAP1 Are Associated with Severe Myopia in Humans

Abstract: Myopia is an extremely common eye disorder but the pathogenesis of its isolated form, which accounts for the overwhelming majority of cases, remains poorly understood. There is strong evidence for genetic predisposition to myopia, but determining myopia genetic risk factors has been difficult to achieve. We have identified Mendelian forms of myopia in four consanguineous families and implemented exome/autozygome analysis to identify homozygous truncating variants in LRPAP1 and CTSH as the likely causal mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 45 publications
0
67
1
2
Order By: Relevance
“…Population-based epidemiological investigations found that the disease is associated with environmental risk factors, such as a close reading distance and less outdoor activity (8,9). With the advent of nextgeneration sequencing, a few of disease genes have been discovered in recent years (18)(19)(20)(21)(22)(23)(24). Because myopia is dependent on both genetics and lifestyle and preschool children have less exposure to environmental risks, we designed this study using a special cohort with EOHM.…”
Section: Discussionmentioning
confidence: 99%
“…Population-based epidemiological investigations found that the disease is associated with environmental risk factors, such as a close reading distance and less outdoor activity (8,9). With the advent of nextgeneration sequencing, a few of disease genes have been discovered in recent years (18)(19)(20)(21)(22)(23)(24). Because myopia is dependent on both genetics and lifestyle and preschool children have less exposure to environmental risks, we designed this study using a special cohort with EOHM.…”
Section: Discussionmentioning
confidence: 99%
“…In these familial cases, linkage analysis has been performed. This approach has proven to be powerful for other familial forms of complex disease such as myopia 72 and systemic lupus erythematosus. 73 To date, 17 distinct potential loci for KC are described; 74 however, only three of these loci have been independently replicated, 5q21, 75,76 5q32 75,77 and 14q11.…”
Section: Geneticsmentioning
confidence: 99%
“…These include Desbuquois dysplasia (MIM: 251450), CTSH-related syndrome (MIM: 116820), and LOXL3-related syndrome (MIM: 607163). [15][16][17] It is likely that GZF1-related myopia is similarly caused by abnormal modeling of the extracellular matrix, as evident by the severe myopia and retinal detachment. It will be of interest to test the contribution of milder variants in GZF1 to myopia in future studies.…”
mentioning
confidence: 99%